Ways of reading : advanced reading skills for students of english literature - Montgomery, Martin; Durant, Alan; Fabb, Nigel; Furniss, Tom; Mills, Sara (London : Routledge, 2000)
Language and Literature
2004-09-06
Keywords: English literature; Reading; College readers; Reading comprehension